Screening of diabetic children for coeliac disease with antigliadin antibodies and HLA typing. Issue 4 (April 1991) - Barera, G; Bianchi, C; Calisti, L; Cerutti, F; Dammacco, F; Frezza, E; Illeni, M T; Mistura, L; Pocecco, M; Prisco, F
Abstract : IgA and IgG antigliadin antibodies were measured in 498 patients with insulin dependent diabetes mellitus and no history of intestinal malabsorption. Thirty patients had abnormal concentrations of antigliadin antibodies; 22 of these had an intestinal biopsy carried out and 16 of the 22 had subtotal villous atrophy suggestive of coeliac disease (prevalence 3.2%). There were no significant differences between patients with coeliac disease and diabetes and diabetic patients with normal IgA antigliadin antibodies in any of the nutritional variables measured, duration of diabetes, and mean insulin requirement. The mean age of onset of diabetes and attainment of expected height for age were both significantly lower in the patients with both diseases. Typing HLA classes I and II was done in 242 patients. The incidence of HLA-B8, DR3, and DQW2, which are commonly associated with both the diseases, is increased when both are present.